Propuesta para la valoración de pymes en Colombia. Estudio de caso en el sector comercial e industrial (2019)
The objective of this article is to propose and apply a valuation method for SMEs in Colombia. A valuation methodology was designed based on the cash flow and was used in the Colombian companies of Carnes CJC S. A. S., Comercial Química Ltda. and Distrimarcas S. A. S. with information from 2002 to 2016. In the companies under study, a strategic analysis was carried out to analyze the success factors and risks of the sector, together with the evaluation of their accounting and financial information to finally make the necessary projections to determine the intrinsic value of SMEs. It was found that the valuation is greater than the value of the assets in the study companies except for CJC S. A. S., which registers a lower value because its free cash flows have decreased due to problems in the management of its operational resources. This valuation model shows that it is consistent with the financial information and the situation of the company, so it is appropriate to apply it in the majority of SMEs in Colombia making the relevant adjustments to the sector and particularities of each.